Unruh-DeWitt detector response across a Rindler firewall is finite - Louko, Jorma (Springer Verlag, 2014)
We investigate a two-level Unruh-DeWitt detector coupled to a massless scalar field or its proper time derivative in (1 + 1)-dimensional Minkowski spacetime, in a quantum state whose correlation structure across the Rindler horizon mimics the stationary aspects of a firewall that Almheiri et al. have argued to ensue in an evaporating black hole spacetime. Within first-order perturbation theory, we show that the detector’s response on falling through the horizon is sudden but finite. The difference from the Minkowski vacuum response is proportional to ω−2 ln(|ω|) for the non-derivative detector and to ln(|ω|) for the derivative-coupling detector, both in the limit of a large energy gap ω and in the limit of adiabatic switching. Adding to the quantum state high Rindler temperature excitations behind the horizon increases the detector’s response proportionally to the temperature; this situation has been suggested to model the energetic curtain proposal of Braunstein et al. We speculate that the (1 + 1)-dimensional derivative-coupling detector may be a good model for a non-derivative detector that crosses a firewall in 3 + 1 dimensions.